2011
DOI: 10.1016/j.nuclphysb.2010.12.013
|View full text |Cite
|
Sign up to set email alerts
|

On non-abelian T-dual geometries with Ramond fluxes

Abstract: We show how to implement T-duality along non-abelian isometries in backgrounds with non-vanishing Ramond fields. When the dimension of the isometry group is odd (even) the duality swaps (preserves) the chirality of the theory. In certain cases a non-abelian duality can result in a massive type-IIA background. We provide two examples by dualising SU(2) isometry subgroups in $AdS_5\times S^5$ and $AdS_3\times S^3\times T^4$. The resultant dual geometries inherit the original AdS factors but have transverse space… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
414
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 189 publications
(427 citation statements)
references
References 58 publications
(94 reference statements)
12
414
0
1
Order By: Relevance
“…In [21] it was shown that when a non-Abelian T-duality is applied to an SU(2) subgroup of isometries of the five-sphere in AdS 5 ×S 5 (or its Z 2 quotient) what results is a target space…”
Section: Jhep11(2015)212mentioning
confidence: 99%
See 4 more Smart Citations
“…In [21] it was shown that when a non-Abelian T-duality is applied to an SU(2) subgroup of isometries of the five-sphere in AdS 5 ×S 5 (or its Z 2 quotient) what results is a target space…”
Section: Jhep11(2015)212mentioning
confidence: 99%
“…This is rather more delicate since one needs to use an appropriate string theory formulation that incorporates the RR background fields. However, it was proposed in [21] that the transformation rules of the RR sector can be deduced using just knowledge of the NS-sector. The crucial point is that left and right movers on the world sheet have different transformation properties under the duality -viz.…”
Section: Jhep11(2015)212mentioning
confidence: 99%
See 3 more Smart Citations